Biocorrosion Behaviour of Carbon Steels by Tropical Microbes in the Presence of Corrosion-Inhibiting Bacterium - Siti Khodijah Chaerun; Intan Nurul Rizki; Wahyu Ardi Hartomo; Bambang Widyanto (HAYATI Journal of Biosciences, 2023)
A set of microbiologically induced corrosion was carried out on different types of carbon steels: AISI 1006 and API 5L X52, iron-oxidizing bacterium and sulfur-oxidizing bacterium, a mixed culture of Alicyclobacillus ferrooxydans SKC/SAA-2 and Aspergillus niger and Comamonas thiooxydans SKC/SAA-1, in the presence of the corrosion-inhibiting bacterium, Pseudomonas plecoglossicida. According to the immersion test experiments, weight loss of API 5L X52 was lower (0.06-0.27%) than AISI 1006 (0.14-0.32%). AISI 1006 showed more detrimental localized pitting corrosion than API 5L X52. During the longer incubation time, the corrosion-inhibiting bacterium was more homogenous and compact, which affected the specimen surface more protective characteristics. The 2-week-old biofilm effectively protected the API 5L X52, as indicated by the low amount and more negligible pitting corrosion. This study will be the first report on the biocorrosion behaviour of carbon steels using different corrosion-causing microbes in the presence of the corrosion-inhibiting bacterium.